Analisis Pengendalian Persedian Bahan Pupuk Pada Kebun Kelapa Sawit Di PT Austindo Nusantara Jaya Agri Binanga - Almi Rahmadani Siregar; Budi Dharma (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to investigate two aspects: (1) the methodology used to record the coal extraction process at PT Austindo Nusantara Jaya Agri Binanga, and (2) the effectiveness and efficiency of the current coal extraction system at PT Austindo Nusantara Jaya Agri Binanga. The research methodology used in this study falls into the domain of cross-sectional and qualitative investigations. The data collection process includes surveys and observations as the main methodology. After starting the verification process, the data entered undergoes analysis through techniques such as data cleaning, data processing, and interpretation of results.The research results show that the application of the Docflow method and fish bone diagrams in fish feeding at PT. Austindo Nusantara Jaya Agri Binanga, along with the use of feeding control procedures such as min-mix (s,S), System (s,Q), System (R,s,S), and System(R,S), is very effective and useful in feeding fish. During the land development phase, per meter counts are carried out to ensure that stocks are monitored and maintained in abundant quantities.